Parents' Strategies in Dealing with Children's Stress Symptoms in Kindergarten during Online Learning - Habibi, M.A Muazar (International Journal of Innovative Research in Medical Science, 2022)
Online learning causes children's stress symptoms, specifically for the preschoolers during COVID-19. This makes parents seek a method in overcoming the difficulties that are faced by students while studying. Therefore, this study aims to examine the parents' strategy in dealing with children's stress symptoms during online learning. A total of 27 respondents were selected using a purposive sampling technique with the criteria of parents and children that are involved in e-learning during COVID-19 in the Batulayar group B kindergarten, Lombok, West Nusa Tenggara, Indonesia. Furthermore data were collected using a survey method. The results showed that most of the children experienced behavioral and cognitive stress symptoms. This critical condition is comprised of three categories including the low, moderate, and the high level that has 15%, 81%, and 4% of children respectively. Moreover, there are 67%, 22%, and 11% of parents prefer to give gifts or rewards, allow play and have recreation, as well as understand their children learning style to deal with stress symptoms while studying at home during COVID-19. Parents have to be more sensitive to their children's conditions to prevent boredom during online learning.